The Effect of Invisible Lost Time on Drilling Performance of Geothermal Wells - Fernandez Sabar Hasudungan Pangaribuan; Sugiatmo Kasmungin; Suryo Prakoso (Journal of Earth Energy Science, Engineering, and Technology, 2020)
Drilling activity has been focused in time on each activity to reach target depth (TD) immediately and efficient in cost. The priority also aimed to Geothermal drilling by doing specific measurement on Invisible Lost Time (ILT) as new focus to perform. Time becomes main aspect which it would affect the cost, therefore it is important to complete the well in time manner. The research was done to analyze the offset well of well A, B, C and D in order to identify Productive Time and Non Productive Time. Key Performance Indicator (KPI) has been identified from each activity also targeted from two wells of well B dan Well D due to time efficiency used during operation. The method used by comparing offset wells then continue to identify each KPI by measuring each activity based on ASCII time and Daily Drilling Report (DDR). The result from offset wells showed inefficiency in time with Flat time 49%, Drilling 42% and non-flat time (NPT) 9% from 28 days without completion. KPI based on the crew performance has confirmed that day shift crew performed better than night shift crew. KPI on rate of penetration (ROP) on day shift crew at 6 m/hr and night crew at 3 m/hr. KPI on Weight to Weight on day shift crew at 28.43 minute/stand faster than night shif crew at 34.65 minute/stand. KPI on Tripping in cased hole on day shift crew at 4.5 minute/stand faster than night crew shift at 4.6 minute/stand. KPI on Tripping in open hole on day shift crew at 2.7 minute/stand faster than night shift crew at 3.7 minute/stand. KPI on Tripping out open hole on day shift crew at 3.0 minute/stand slower than night shift crew at 2.8 minute/stand. KPI on Tripping out cased hole on day shift crew at 3.36 minute/stand faster than night crew shift at 3.74 minute/stand. ILT from both wells to 20 % or 5 days inefficiency on each well. It detects of potential savings to 10 billion rupiah from both wells.